The Sectarian Iceberg?. Issue 3 (August 2015) - Rosie, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> This article situates the contemporary evidential position on Scotland's sectarianism within some longer-term and ongoing debates. It does so by addressing three key aspects of sectarianism in Scotland. Firstly it explores long-standing concerns about sectarianism in Scotland, and the puzzle that sectarianism frequently seems to be someone else's problem. It then outlines some central evidential claims made about sectarianism in the 1980s and why our increasing knowledge about religion in Scotland's social structure appear to bear them out. Finally, the article concludes by questioning how far we can conceive of 'Protestants' and 'Catholics' as divided in the personal, informal and intimate spheres of contemporary Scottish life.